Environmental Literacy: A Bibliometric Analysis - Rita Bekti Utami; Suhartini; Arina Zaida Ilma; Rizqy Aisyah Leonia; Eni Suyantri (Jurnal Penelitian Pendidikan IPA, 2025)
Environmental literacy is important in modern education to encourage individuals to become more environmentally aware. This research aims to reveal research trends, research methods, education levels, and countries that conduct environmental literacy research. The technique used is bibliometric analysis. Sixty-eight documents indexed in the Scopus database were analyzed using VOSviewer and Biblioshiny, with publication years ranging from 2019 to 2024. The findings show that the survey method is dominant in environmental literacy research. Environmental literacy measurements in the adult group account for the largest number. Publications about environmental literacy increased significantly in 2020–2021 and 2023–2024. The United States is the leading country in environmental literacy research. Environmental education and environmental literacy are trending topics in this field of research. This shows that there is an increasing research focus on environmental issues in the educational context.